Essays on development and biodiversity conservation in Sub-Saharan Africa - (:unkn) unknown (My University, 2014)
This thesis is composed of a set of research in applied economics that enroll in the contemporary field of economics of biodiversity. The thesis focuses specifically on the links between economic development, local welfare and biodiversity conservation in sub-Saharan Africa region. An introductory chapter presents the subject of the thesis as well as the research field and situates our contribution.The rest of the thesis is composed of two parts divided into macroeconomic studies and case studies. Part 1 (composed of chapter 2 and chapter 3) addresses the link biodiversity and development under a macroeconomic perspective by taking into account spatial interactions between countries. In chapter 2, we examine the impact of development in sub-Saharan Africa on biodiversity using recent indicators on threatened species. In chapter 3, we focus on the mechanisms that support public conservation policies in Sub-Saharan Africa and tested the effect of tourism, environmental aid and spillover effects on conservation effort. Part 2 (composed of chapter 4 and chapter 5) presents two case studies in Ivory Coast. Chapter 4 presents a cost benefit analysis using contingent valuation and market price method. It evaluates the costs and benefits of conservation for local populations. In chapter 5 we examine people's preferences for conservation and identify key factors that determine local preferences. In the last chapter we draw implications of results and present potential extensions of this thesis.
Keywords: African Research